Theoretical Study on the Mechanism for the Formation of Nitro Compounds in Red Oil - Meng-Ke Tian; Shuang-Ling Tang; Hong-Bin Tang; Xue-Hai Ju (Journal of Chemistry)
The mechanisms involved in reactions between methane, n-hexane, n-butanol, cyclohexane, and nitric acid were explored by density functional theory calculations. All the calculations in gas phase and n-tributyl phosphate (TBP) solvent were performed at the B3LYP/6–311++G∗∗ and CCSD(T)/6–311++G∗∗ levels of theory. The results showed that TBP has an important effect on the reactions between nitric acid and alkanes or butanol. The reactions were considered as that the radicals (·NO2 and ·NO3 radicals are formed via the HNO3 decomposition under irradiation) initiate the H-atom depletion of the reactants (R), and the produced radicals in red oil combine with ·NO2 radical to form the nitro compounds spontaneously. The rate constants of reactions R + ·NO2 and R + ·NO3 differ substantially, the rate constants of the latter being much larger than those of the former. In the reactions of R + ·NO3, the transition states and products are 20 kJ/mol and 100 kJ/mol or more stable than the reactants, respectively, but the reactions of R + ·NO2 need to overcome energy barriers over 25 kJ/mol. The formations of products mainly depend on the reactions of R + ·NO3. For the same type of alkanes (either chain or cyclic ones), the lower the relative stabilities of carbon-centered radicals are, the more reactive the alkanes are. Cyclohexane is the most competitive species, followed by n-butanol, n-alkanes, and methane which are the least competitive.